Metaphorical Translation and Cultural Cognition in Mazu Texts: Insights from Sino-English Translation - Zhang, Danke (CINEFORUM, 2025)
Spiritual experiences like cultivation practices, divine manifestations and dream revelations are commonly recorded in Mazu scriptures using metaphorical and analogical language based on cognitive models. These metaphorical characteristics make the process of translation of Mazu-related texts a two-level process of metaphoric interpretation and re-conceptualization. Using the case study of Tianfei niangma zhuan (The Biography of the Empress of Heaven) and Tianfei xiansheng lu (Records of the Miracles of the Heavenly Empress), this paper explores the cognitive features of the metaphorical language of the Mazu scriptures. It posits that the use of Sino-English-which is defined as a literal translation accompanied by an interpretative annotations- can be a good approach to the translation of culturally specific religious ideas. This is not only useful in bridging conceptual gaps in intercultural communication, but also to aid in the transference and recognition of the traditional Chinese religious culture across the world.